The approximators about, at least and nearly as interpersonal devices in nineteenth-century women’s instructive texts - Elena Quintana Toledo (Revista de Lingüística y Lenguas Aplicadas)
This paper aims at describing how about, at least and nearly are used in the nineteenth-century subcorpus of the Corpus of Women’s Instructive Texts in English, which gathers instructional texts exclusively written by women. While still retaining their approximative sense, about, at least and nearly have a large potential to build and maintain writer-reader interpersonal relationships. The most frequent collocational patterns have been firstly identified by using corpus tools to later analyse the major pragmatic functions of specific examples following Zhang’s (2015) framework for elastic language. Findings reveal that collocations with numerical expressions are common to about, at least and nearly while other patterns only emerge with about and nearly. It also seems that pattern and function are tightly interwoven. In general, the approximators surveyed here fulfill a variety of interpersonal functions, most notably, just-right elastic, rapport elastic, mitigating elastic, self-protection elastic, and intensifying elastic.